Investigation of lead and iron removal from groundwater using sapropel and quartz sand - Heang, Sorphea; Albrektienė, Ramunė; Paliulis, Dainius (International Conference “Environmental Engineering”, 2020)
In Prey Nop district of Cambodia, a district in coastal area, it was observed that concentration of iron and lead in groundwater was higher than permissible values. Lead is a highly toxic heavy metal, while iron is an element causing several problems related to the deterioration of taste and aesthetic appearance of water and the capacity reduction of water supply pipelines. Therefore, this article investigates the effectiveness of the technology for removing lead and iron from groundwater using the cheapest materials like sapropel and sand. In this study, different doses of sapropel (0.1, 0.2, 0.4, 0.5, 0.6, 0.8, 1, 2, 3, 4, 5 and 6 g/L), different durations of sorption processes (30, 60, 90, 120 and 150 min) and a laboratory bench for iron filtration filled with quartz sand were used for lead and iron ions removal. Results from the bench tests showed that both iron and lead were removed at efficiencies of 70 and 97%, and their concentrations did not exceed the permissible levels by using the lowest dose of 0.1 g/L of sapropel for sorption of lead and filtration through quartz sand filters for iron removal.